Prevalensi Infeksi Protozoa Saluran Pencernaan Pada Kucing Lokal (Felis catus) Di Denpasar - Putu Titin Evi Sucitrayani; Ida Bagus Made Oka; Made Dwinata (Buletin Veteriner Udayana, 2014)
Cat is one of the pets which many people love to looking after.  A lot of people looking after cat but so many of them don’t pay much attention to cats wealth, this makes them become stray cat. The most common gastrointestinal protozoa in cat is Giardia felis, Cryptosporadium felis, Sarcocystis spp, Hammondia hamondi, Toxoplasma gondii, and Isospora spp. The purpose of this research is to know the prevalence of gastrointestinal protozoa infection in local home cat and stray cat in Denpasar. This research used 80 samples of cat feces, 40 home cat feces and 40 stray cat feces. Samples examined using float concentration method, with saturated sodium chloride. From 80 examined samples, 25 samples (31,3 %) infected with gastrointestinal protozoa. For home cat, from 40 examined samples 9 samples  (22,5%)  infected with gastrointestinal protozoa, meanwhile from stray cat, 16 samples (40 %)  infected from gastrointestinal protozoa.